Analisis Formularium RSUD Cimacan Tahun 2017 - Aritonang, Juliana (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2017)
Hospitals must provide comprehensive, integrated and sustainable health services which in the organization of the hospital is inseparable from pharmaceutical services. The need for the provision and use of qualified and rational medicines is regulated in the formulary system where the drugs used are contained in the formulary book. The purpose of this study was to analyze the formulary of RSUD Cimacan seen from the preparation, maintenance and evaluation of formulary drugs. Evaluation of formulary drugs by performing ABC analysis of use, investment, critical index and VEN to obtain the result of proposed revision formulary of RSUD Cimacan. This research uses qualitative approach. The result is the process of formulary of RSUD Cimacan not optimal, procedure of maintenance of formulary already exist but not yet complete, procurement and prescription not according to formulary. 495,690 non-formulary drug use and 201 kinds of non-formulary drugs were provided in pharmaceutical installations. There are 322 kinds of formulary drugs used (43%), there are 21 types of drugs with an investment value of RP. 3.001.658.694. Only 31 types of drugs are very critical and 39 types of drugs are Vital to patient care.